Formulation of a numerical model of insertion and retention forces in cantilever hook snap-fits joints - Siti Sarah, Abdul Manan (2024)
The advancement of technology has contributed significantly to the engineering and automotive industries. The electrical and electronic industries often utilize snap-fit applications such as door handle bezels and acrylic glass containers. Snap-fit is a joining technique used to combine two or more parts together, either plastic to plastic or plastic to other materials. Typically, snap-fit is directly formed into the part as it does not require external energy sources. Snap-fit can be separable or inseparable depending on the design usage. Snap-fit has three types: cantilever, torsion, and annular, and in this study, the focus is on the cantilever type of snap-fit. Cantilever snap-fit is widely used in industries due to its simple design. In this study, snap-fit parameters are examined in relation to insertion force and retention. Several parameters affecting the design of the snap-fit such as the thickness of beam (Tb), length of the beam (Lb), width of the beam (Wb), base radius (Rb), insertion angle (α) and retention angle (β). In this study, ABS material is used because ABS is a thermoplastic material with low production costs and resistance to chemicals, stiffness, and impact. Snap-fit is also simulated using nonlinear simulation based on contact surface analysis. Cantilever snap-fit is designed using Autodesk Inventor software and simulated using ANSYS software to generate insertion and retention force results. Subsequently, it is printed using a 3D printer and tested using a UTM machine, and simulation and experimental results are compared. Snap-fit is tested to evaluate the performance of proposed numerical models based on design factors, insertion force, and retention. It is found that increasing the insertion and retention angles increases the insertion and retention force of the cantilever snap-fit. The results show that the snap-fit from Model 10 has the lowest insertion force value of 3.3399N, while the lowest retention force value is from Model 2 with a value of 1.7219N. With the obtained results, it can be determined which designs contribute less to injury during assembly and pressure loading. In conclusion, snap-fit is widely used in daily life, and this study can have an impact on the electrical, automotive, and other manufacturing fields to produce more optimal, safe, and suitable snap-fit designs. The percentage of error less than 10% indicates that this study is applicable and referenceable.